Positive electrode, method for preparing positive electrode, and lithium secondary battery comprising positive electrode
By setting a lithium metal layer on the positive electrode of the lithium ion secondary battery and carrying out a calendering process, inserting lithium ions into the positive electrode active material layer, the volume change of silicon active material particles and the existence of prelithiation technology in the lithium ion secondary battery are solved. The risk of fire has achieved an extension of battery life and an improvement in safety.
Patent Information
- Application Number
- CN202380041025.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-12
- Filing Date
- 2023-08-11
- Publication Date
- 2024-12-13
AI Technical Summary
In existing lithium-ion secondary batteries, the volume changes of silicon-type active material particles lead to a shortening of battery life, and the prelithiation process has the risk of ignition.
By setting a lithium metal layer on the positive electrode and performing a calendering process, lithium ions are embedded in the positive electrode active material layer, reducing the amount of lithium ions embedded in the negative electrode, avoiding the alloying reaction between lithium and silicon and the reaction between lithium and water, and reducing the risk of ignition. And improve the battery life characteristics.
It effectively inhibits the generation of lithium side reactions in lithium-ion secondary batteries, reduces lithium losses, extends battery life, improves energy density, and reduces safety hazards during battery preparation.
Smart Images

Figure CN119137760A_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to Korean Patent Application No. 10-2022-0101636, filed on August 12, 2022, the disclosure of which is incorporated herein by reference. Technical Field
[0003] The present invention relates to an over-lithiated cathode, a method of preparing a cathode, and a lithium secondary battery including the cathode. Background Art
[0004] Due to the rapid increase in the use of fossil fuels, the demand for the use of alternative or clean energy has been increasing, and as part of this trend, the most actively studied field is the field of power generation and power storage using electrochemical reactions.
[0005] Currently, typical examples of electrochemical devices using electrochemical energy can be secondary batteries, and the trend is that their fields of use are becoming larger. In recent years, with the development of technologies and the increase in demand for portable devices such as portable computers, mobile phones, and cameras, the demand for ion secondary batteries as an energy source has increased significantly, and among these secondary batteries, lithium-ion secondary batteries with high energy density, that is, high capacity, have been extensively studied and have been commercialized and widely used.
[0006] Generally, a lithium-ion secondary battery is composed of a cathode, an anode, an electrolyte, and a separator. The anode contains an anode active material into which lithium ions released from the cathode are embedded and de-embedded, and silicon-based active material particles having a large discharge capacity can be used as the anode active material. The silicon-based active material particles may correspond to silicon (Si) or SiO x (0 < x < 2). The silicon-based active material particles have the advantages of a large theoretical capacity and low price. However, because the silicon-based active material particles have an excessive volume change during battery operation, the disadvantage is that the life of the battery rapidly shortens as the battery cycles proceed.
[0007] Accordingly, in order to minimize the volume change of the silicon-based active material particles, there is a method of using only a part of the total capacity of the silicon-based active material particles. For this purpose, a so-called prelithiation process is used, in which lithium ions are pre-embedded into the anode containing the silicon-based active material particles. Specifically, if lithium ions are embedded into the anode by a method such as transferring lithium metal to the anode, when the lithium ions react at irreversible sites of the anode, the total capacity of the anode can be reduced to the level of the reversible capacity. Accordingly, because the amount of lithium ions embedded during battery operation can be appropriately reduced to the level required for battery operation, the volume change of the silicon-based active material particles can be minimized.
[0008] However, in the process of pre-lithiation by providing lithium metal on the surface of the negative electrode, excessive heat is generated due to the alloying reaction between lithium and silicon, and the possibility of fire due to the reaction between lithium and moisture is also increased. In addition, in the process of grooving and punching the negative electrode, the reaction area between lithium and silicon-based active materials can be increased to further increase the possibility of fire.
[0009] There is also the potential for fire caused by pre-lithiated silicon-based active material particles.
[0010] Therefore, a new technology is needed that can suppress the possibility of overheating and fire while improving the life of the battery by pre-intercalating lithium ions into the negative electrode before the battery is operated. Summary of the invention
[0011] Technical issues
[0012] One aspect of the present invention provides a positive electrode, in which the energy density and life characteristics of a battery can be improved, and the safety in a battery manufacturing process can be improved.
[0013] Another aspect of the present invention provides a method for preparing a positive electrode.
[0014] Another aspect of the present invention provides a lithium secondary battery including a positive electrode.
[0015] Technical Solution
[0016] According to one embodiment of the present invention, there is provided a positive electrode including a positive electrode active material layer including a positive electrode active material, and the positive electrode satisfies Formula 1.
[0017] [Formula 1]
[0018] 1.2≤I
[003] / I
[200] ≤2.0
[0019] In formula 1,
[0020] I
[003] is the integrated value of the maximum peak in the 2θ range of 17.0° to 19.0° appearing during X-ray diffraction (XRD) measurement on the surface of the positive electrode active material layer, and
[0021] I
[200] It is the integrated value of the maximum peak in the 2θ range of 43° to 45° appearing during XRD measurement on the surface of the positive electrode active material layer.
[0022] According to another embodiment of the present invention, there is provided a method for preparing a positive electrode, the method comprising:
[0023] Step P1: disposing a transfer stack including a base film and a lithium metal layer disposed on the base film on a preliminary positive electrode including a preliminary positive electrode active material layer to form a positive electrode structure, such that the lithium metal layer and the preliminary positive electrode active material layer are in contact with each other;
[0024] Step P2: rolling the positive electrode structure; and
[0025] Step P3: Removing the base film from the transfer stack after calendering,
[0026] Here, the pressure applied to the positive electrode structure during the rolling is in the range of 10 kgf / cm to 90 kgf / cm.
[0027] According to another embodiment of the present invention, there is provided a lithium secondary battery, the lithium secondary battery comprising: a positive electrode; a negative electrode; a separator disposed between the positive electrode and the negative electrode; and an electrolyte,
[0028] The positive electrode includes a positive electrode active material layer, the positive electrode active material layer includes a positive electrode active material, and the positive electrode satisfies the following formula 1.
[0029] [Formula 1]
[0030] 1.2≤I
[003] / I
[200] ≤2.0
[0031] In formula 1,
[0032] I
[003] is the integrated value of the maximum peak in the 2θ range of 17.0° to 19.0° appearing during XRD measurement on the surface of the positive electrode active material layer, and
[0033] I
[200] It is the integrated value of the maximum peak in the 2θ range of 43° to 45° appearing during XRD measurement on the surface of the positive electrode active material layer.
[0034] According to another embodiment of the present invention, there is provided a method for preparing a lithium ion secondary battery, the method comprising:
[0035] Step B1: preparing a preliminary lithium ion secondary battery, the preliminary lithium ion secondary battery comprising a positive electrode; a negative electrode; a separator disposed between the positive electrode and the negative electrode; and an electrolyte; and
[0036] Step B2: Activate the prepared lithium-ion secondary battery,
[0037] The method for preparing the positive electrode comprises:
[0038] Step P1: disposing a transfer stack including a base film and a lithium metal layer disposed on the base film on a preliminary positive electrode including a preliminary positive electrode active material layer to form a positive electrode structure, such that the lithium metal layer and the preliminary positive electrode active material layer are in contact with each other;
[0039] Step P2: rolling the positive electrode structure; and
[0040] Step P3: Removing the base film from the transfer stack after calendering,
[0041] Here, the pressure applied to the positive electrode structure during the rolling is in the range of 10 kgf / cm to 90 kgf / cm.
[0042] Beneficial Effects
[0043] In the positive electrode according to the present invention, a lithium metal layer is disposed on the positive electrode by a transfer method, and the lithium ions of the lithium metal layer are embedded in the positive electrode active material layer by a rolling process applying an appropriate level of pressure. Therefore, the positive electrode satisfies the above formula 1. If a preparatory lithium ion secondary battery is prepared by using a positive electrode prepared by the above method and the preparatory lithium ion secondary battery is activated, the lithium ions react and fill the irreversible sites of the negative electrode because the lithium ions embedded in the positive electrode are transferred to the negative electrode. Therefore, the amount of lithium ions embedded in the negative electrode during battery operation can be appropriately reduced to the level required for battery operation. Therefore, because the available range of the negative electrode capacity can be reduced while maintaining the battery capacity, the excessive volume change of the silicon-based active material particles can be suppressed, and the life characteristics of the battery can be improved.
[0044] In addition, because the pre-lithiation is not carried out by contacting the lithium metal layer with the negative electrode, but the lithium metal layer is transferred to the positive electrode and rolled, and then the lithium ions embedded in the positive electrode are transferred to the negative electrode during the activation process of the battery, the phenomenon of excessive heat generated due to the alloying reaction of lithium and silicon at the negative electrode can be avoided, and the possibility of fire caused by the reaction between lithium and moisture can be significantly reduced. In addition, because lithium ions are not embedded in the negative electrode during the grooving and punching of the negative electrode (because pre-lithiation is not performed), the possibility of fire during the grooving and punching process can be significantly reduced.
[0045] In particular, since the lithium ions of the lithium metal layer are embedded in the positive electrode active material layer at an appropriate level of pressure during the preparation of the positive electrode, the degree of cracking of the positive electrode active material can be reduced, thereby improving the life characteristics of the lithium ion secondary battery and improving the energy density. In addition, since the lithium side reaction products can be reduced, the amount of lithium loss can be reduced, thereby improving the long-term life characteristics of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 is a schematic diagram showing step P1 in the method for preparing a positive electrode according to one embodiment of the present invention.
[0047] Figure 2 is a schematic diagram showing step P1 of using a transfer stack including a polymer layer in a method of preparing a positive electrode according to an embodiment of the present invention.
[0048] Figure 3 is a schematic diagram showing step P2 in the method for preparing a positive electrode according to one embodiment of the present invention.
[0049] Figure 4 is a schematic diagram showing step P3 in the method for preparing a positive electrode according to one embodiment of the present invention.
[0050] Figure 5 This is a graph showing the X-ray diffraction (XRD) measurement results of the positive electrode of Example 1-1 of the present invention.
[0051] Figure 6 It is a graph of the XRD measurement results of the positive electrode of Example 1-2 of the present invention.
[0052] Figure 7 This is a graph showing the XRD measurement results of the positive electrode of Comparative Example 1-2 of the present invention. DETAILED DESCRIPTION
[0053] Hereinafter, the present invention will be described in more detail to enable a clearer understanding of the present invention.
[0054] It should be understood that, on the basis of the principle that the inventor can appropriately define the meaning of words or terms to best explain the present invention, the words or terms used in the specification and claims should not be interpreted as the meanings defined in commonly used dictionaries, and it should also be understood that the words or terms should be interpreted as having meanings consistent with their meanings in the context of the relevant technology and the technical idea of the present invention.
[0055] The terms used herein are for the purpose of describing specific exemplary embodiments only and are not intended to limit the present invention.In the present specification, unless otherwise indicated, a term in the singular form may include a plural form.
[0056] It should be further understood that when used in this specification, the terms "include", "comprises" or "has" are intended to clarify the existence of the stated features, numbers, steps, elements or a combination thereof, but do not exclude the existence or addition of one or more other features, numbers, steps, elements or a combination thereof.
[0057] D in this manual 50 It can be defined as the particle size at which the cumulative volume in the particle size distribution curve is 50%. For example, D50 This can be measured using laser diffraction, which can typically measure particle sizes from submicrometers to several millimeters and can produce highly reproducible and high-resolution results.
[0058] The X-ray diffraction (XRD) measurement in this specification is performed as follows.
[0059] The wavelength of X-rays generated by copper (Cu) Kα was used, and the wavelength (λ) of the light source was 0.15406 nm.
[0060] 1) Measurement equipment and conditions: Bruker D8 Endeavor (Cu target 40 kV, 40 mA, 1.54 Å) LynxEye position sensitive detector (4.1° slit)
[0061] 2) Experimental process
[0062] 2-1) Preparation for cutting / cross sectioning: Prepare the sample by cutting it to the size of the sample holder.
[0063] 2-2) Preparation for sample mounting: The sample (positive electrode) was attached to a glass plate using double-sided tape so that there was no gap therebetween, and then mounted using rubber clay and a holder formed of PMMA.
[0064] 2-3) Powder XRD (Bruker D8 Endeavor): The fixed divergence slit (FDS) was adjusted to 0.5° according to the sample size, and the powder XRD was measured every 0.0156° in the 2θ range of 10° to 125° for 0.3 seconds.
[0065] 2-4) XRD phase analysis: Determine the phases present in the sample by comparing with a database (PDF).
[0066] 2-5) Rietveld analysis: Rietveld refinement is performed using a complete structural model of the phases present in the sample.
[0067] <Positive electrode>
[0068] A positive electrode according to one embodiment of the present invention includes a positive electrode active material layer including a positive electrode active material, and may satisfy Formula 1 below.
[0069] [Formula 1]
[0070] 1.2≤I
[003] / I
[200] ≤2.0
[0071] In formula 1,
[0072] I
[003] is the integrated value of the maximum peak that appears in the 2θ range of 17.0° to 19.0° during XRD measurement on the surface of the positive electrode active material layer, and
[0073] I
[200] is the integrated value of the maximum peak that appears in the 2θ range of 43° to 45° during XRD measurement on the surface of the positive electrode active material layer.
[0074] The positive electrode may include a positive electrode active material layer. The positive electrode active material layer itself may constitute the positive electrode, but the positive electrode active material layer may be provided on a positive electrode current collector.
[0075] There is no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause adverse chemical changes in the battery, and for example, the following can be used: stainless steel, aluminum, nickel, titanium, fired carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. In addition, the positive electrode current collector generally may have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. For example, the positive electrode current collector can be used in various shapes such as films, sheets, foils, meshes, porous bodies, foams, non-woven fabric bodies, etc.
[0076] The positive electrode active material layer may be provided on one surface or both surfaces of the positive electrode current collector. The positive electrode active material layer may contain a positive electrode active material.
[0077] The positive electrode active material is a material in the form of particles that can cause an electrochemical reaction, and among them, it may be a lithium transition metal oxide. For example, the positive electrode active material may contain at least one selected from the following: layered compounds substituted with at least one transition metal such as lithium cobalt oxide or lithium nickel oxide; lithium manganese oxide substituted with at least one transition metal; composed of Li 1+x [Ni a Co b Mn c M 1 (1-a-b-c) O (2-d) A d (where M 1 is at least one selected from aluminum (Al), magnesium (Mg), chromium (Cr), titanium (Ti), silicon (Si), and yttrium (Y), A is at least one selected from fluorine (F), phosphorus (P), and chlorine (Cl), and -0.5 ≤ x ≤ 0.5, 0.1 ≤ a ≤ 1, 0.05 ≤ b ≤ 0.5, 0.05 ≤ c ≤ 0.5, 0 ≤ d ≤ 0.2 and 0 < a + b + c ≤ 1) represents a lithium nickel cobalt manganese composite oxide; composed of Li[Ni 1-y M 2 y O2 (where M2 It may be at least one selected from cobalt (Co), manganese (Mn), Al, copper (Cu), iron (Fe), Mg, boron (B), Cr, zinc (Zn) and gallium (Ga), and 0.01≤y≤0.7) represented by a lithium nickel-based oxide; and Li 1+z [M 3 1-q M 4 q ]PO 4-r X r (Among them, M 3 is at least one selected from Fe, Mn, Co and nickel (Ni), M 4 is at least one selected from Al, Mg and Ti, X is at least one selected from F, sulfur (S) and nitrogen (N), and -0.5≤z≤0.5, 0≤q≤0.5 and 0≤r≤0.1).
[0078] Specifically, the positive electrode active material may include a layered structured lithium nickel-based transition metal composite oxide, and the lithium nickel-based transition metal composite oxide may include a compound of the following Chemical Formula 1, and more specifically, may be a compound of the following Chemical Formula 1.
[0079] [Chemical formula 1]
[0080] Li 1+x [Ni a Co b Mn c M 1 (1-a-b-c) ]O (2-d) A d
[0081] In Chemical Formula 1,
[0082] M 1 It is at least one selected from Al, Mg, Cr, Ti, Si, and Y, and specifically may be Al.
[0083] A is at least one selected from F, P and Cl, and may be specifically F.
[0084] x may satisfy -0.5≤x≤0.5, specifically -0.3≤x≤0.3.
[0085] a may satisfy 0.6≤a<1, specifically 0.7≤a≤0.9.
[0086] b may satisfy 0.03≤b≤0.1, specifically 0.05≤b≤0.1.
[0087] c can satisfy 0.03 ≤ c ≤ 0.1, specifically 0.05 ≤ c ≤ 0.1.
[0088] d can satisfy 0 ≤ d ≤ 0.1, specifically 0 ≤ d ≤ 0.05.
[0089] a, b, and c satisfy 0 < a + b + c ≤ 1, specifically a + b + c = 1.
[0090] The compound of Chemical Formula 1 can be in the form of particles.
[0091] The layered structured lithium nickel-based transition metal composite oxide can be in the form of secondary particles in which a plurality of primary particles are combined with each other. Specifically, the compound of Chemical Formula 1 can be in the form of secondary particles in which 10 or more primary particles are combined with each other. Therefore, there is an effect that lithium can be uniformly inserted into and deintercalated from the positive electrode active material.
[0092] D of the lithium nickel-based transition metal composite oxide 50 can be from 5 μm to 15 μm, particularly from 7 μm to 12 μm, and more particularly from 9 μm to 10 μm. D 50 can be the D of the secondary particles 50 . Since the positive electrode paste is easily dispersed when the above range is satisfied, the positive electrode active material layer can be uniformly coated.
[0093] The content of the positive electrode active material in the positive electrode active material layer can be from 90% by weight to 99% by weight, particularly from 92% by weight to 98% by weight, and more particularly from 95% by weight to 98% by weight.
[0094] The positive electrode active material layer may further contain a positive electrode binder. The positive electrode binder improves the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode current collector. Specific examples of the binder can be polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and any one or a mixture of two or more thereof can be used.
[0095] The content of the positive electrode binder in the positive electrode active material layer can be from 0.5% by weight to 5.0% by weight, particularly from 1.0% by weight to 2.5% by weight, and more particularly from 1.0% by weight to 2.0% by weight.
[0096] The positive electrode active material layer may also include a positive electrode conductive material. The positive electrode conductive material is used to provide conductivity to the electrode, wherein any conductive material may be used without particular limitation, as long as it has suitable electronic conductivity and does not cause adverse chemical changes in the battery. Specific examples of positive electrode conductive materials may be: graphite such as natural graphite or artificial graphite; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and carbon fiber; powders or fibers of metals such as copper, nickel, aluminum and silver; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one thereof or a mixture of two or more thereof may be used.
[0097] The positive electrode conductive material may be included in an amount of 0.5 wt % to 30.0 wt %, specifically 0.5 wt % to 10.0 wt %, and more specifically 1.0 wt % to 4.0 wt % in the positive electrode active material layer.
[0098] The positive electrode active material layer may also contain lithium byproducts. The lithium byproducts correspond to byproducts formed by transferring the lithium metal layer to the positive electrode active material layer and rolling it during the preparation of the positive electrode. Specifically, the positive electrode active material layer may contain any one selected from the following: Li3N, Li2CO3 and LiOH.
[0099] In addition, when the lithium metal layer is transferred to the positive electrode active material layer, the crystal structure of a portion of the positive electrode active material in the positive electrode active material layer may change due to overlithiation. In particular, for the layered structured positive electrode active material represented by LiMO2, there is a LiMO2-type layered structure corresponding to the space group R-3m, a Li2MO2-type layered structure corresponding to the space group P-3m1 (T1) is formed due to excess lithium, and a rock salt structure corresponding to the space group Fm-3m represented by MO can be formed. These crystal structures can be determined according to the rolling conditions and the amount of lithium by-products generated by overlithiation, and the amount of lithium by-products and the rolling conditions need to be appropriately adjusted to meet the following conditions in the figure obtained by XRD described later.
[0100] The positive electrode can satisfy the following formula 1.
[0101] [Formula 1]
[0102] 1.2≤I
[003] / I
[200] ≤2.0
[0103] In formula 1, I
[003] It is the integral value of the maximum peak in the 2θ range of 17.0° to 19.0° appearing during XRD measurement on the surface of the positive electrode active material layer, specifically, the 2θ range in which the maximum peak appears may be 17.5° to 18.5°, and may be 17.5° to 18.2°. In addition, I
[200] is an integrated value of a maximum peak in a 2θ range of 43° to 45° appearing during XRD measurement on the surface of the positive electrode active material layer, and the 2θ range in which the maximum peak appears may be 43.5° to 44.5° and may be 43.7° to 44.3°.
[0104] In addition, according to one embodiment of the present invention, I of Formula 1
[003] / I
[200] It may preferably be 1.21 or more, 1.22 or more, 1.23 or more, or 1.24 or more, and may preferably be 1.80 or less, 1.70 or less, 1.65 or less, 1.60 or less, or 1.58 or less.
[0105] For I
[003] , which is a peak derived from the positive electrode active material corresponding to the layered structure of the hexagonal crystal corresponding to the space group R-3m, wherein the intensity of the peak may vary depending on the degree of overlithiation, the degree of phase transition to the rock salt phase (Fm-3m), and the degree of generation of lithium by-products, and I
[200] It is a peak that appears due to the transformation into a crystal structure of a rock salt phase, wherein it can be determined by the degree of cracking of the positive electrode active material due to rolling, the degree of cracking of the positive electrode active material due to lithium transfer, and the degree of generation of lithium by-products.
[0106] Usually, in which I
[003] Big and I
[200] In the case of a small I, it can be evaluated as a positive electrode active material having an excellent crystal structure. However, in the case of overlithiation, since overlithiation requires a rolling process, damage to the positive electrode active material is caused by lithium transfer, and lithium by-products are generated on the surface, it is difficult to simply evaluate the positive electrode active material having a large I.
[003] Value and small I
[200] The values are excellent, and it may be difficult to improve the values in a desired direction.
[0107] However, according to one embodiment of the present invention, in the case where the rolling pressure and the degree of overlithiation are adjusted during the preparation of the positive electrode to have a numerical range as described above, the most desirable performance can be achieved when the degree of damage to the positive electrode active material particles, the increase or decrease in resistance due to lithium by-products, or the capacity loss of the positive electrode active material due to the generation of a rock salt phase are comprehensively considered.
[0108] In the process of preparing the positive electrode of the present invention, the lithium metal layer is transferred to the positive electrode active material layer, and then the positive electrode containing the lithium metal layer is rolled under a pressure of 10 kgf / cm to 90 kgf / cm, so that the lithium ions of the lithium metal layer are embedded in the positive electrode active material layer. In this process, the lithium ions generate lithium byproducts. The positive electrode satisfies Formula 1 and can be considered to mean that during the preparation of the positive electrode of the present invention, the lithium metal layer is transferred to the positive electrode active material layer and the positive electrode is rolled under a pressure of 10 kgf / cm to 90 kgf / cm.
[0109] If the pressure during rolling is less than 10 kgf / cm, it is difficult to insert lithium into the positive electrode at a desired level because the lithium metal layer of the transfer stack is not effectively transferred to the positive electrode during the preparation of the positive electrode.
[003] / I
[200] It may be greater than 2.0. Therefore, since the amount of lithium transferred to the negative electrode during the activation process is reduced, and since lithium remains on the surface without diffusing into the active material layer and a large amount of lithium by-products caused by reaction with the electrolyte or air in the atmosphere are generated, the capacity is not improved due to the increase in the amount of lithium loss, it is difficult to improve the life characteristics of the battery, and the resistance of the electrode may also increase due to the by-products.
[0110] On the contrary, if the pressure during rolling is greater than 90 kgf / cm, cracking of the positive electrode active material may occur excessively because the diffusion rate of lithium is too large, and accordingly, the positive electrode capacity may decrease and the life characteristics of the battery may deteriorate. In addition, even in this case, there is a problem of an increase in damaged positive electrode active materials, a large amount of lithium by-products may be formed due to a side reaction in which Li2MO2 crystals decompose into Li2O and MO to reduce the capacity of the positive electrode and deteriorate the long-term life characteristics of the battery, and since the rock salt phase also increases, problems such as reduced capacity, increased resistance, and shortened life may occur. For example, if the pressure during rolling is greater than 90 kgf / cm, I
[003] / I
[200] Probably less than 1.2.
[0111] That is, in the case where the positive electrode satisfies the above Formula 1, since sufficient lithium is supplied to the positive electrode, pre-lithiation of the negative electrode can be smoothly performed during battery activation, and there is an advantage in that the capacity of the positive electrode and the life characteristics of the battery are improved.
[0112] The positive electrode may also include a lithium metal layer disposed on the positive electrode active material layer. The lithium metal layer serves to supply lithium ions to the positive electrode active material layer. Specifically, the positive electrode active material layer may be disposed between the positive electrode current collector and the lithium metal layer. The lithium metal layer may be in contact with the positive electrode active material layer. The lithium metal layer includes solid-phase lithium metal, and the lithium metal layer may be specifically formed of solid-phase lithium metal.
[0113] The positive electrode may also include a polymer layer disposed on the positive electrode active material layer. The polymer layer may effectively peel off the lithium metal layer from the transfer stack during the preparation of the positive electrode and facilitate the transfer of the lithium metal layer to the positive electrode active material layer. That is, the polymer layer may be separated from the transfer stack together with the lithium metal layer to be disposed on the positive electrode active material layer. The polymer layer may be present in contact with the positive electrode active material layer, or the lithium metal layer may be present between the polymer layer and the positive electrode active material layer.
[0114] The polymer layer may be at least one selected from the group consisting of polyethylene terephthalate (PET), polyimide (PI), poly(methyl methacrylate) (PMMA), polypropylene, polyethylene, and polycarbonate. Therefore, in a secondary battery comprising a positive electrode, since the polymer layer can be dissolved in the electrolyte contained in the secondary battery, the resistance of the battery can be prevented from increasing. In particular, the polymer layer may include PMMA, in which case the above-mentioned effect may be further improved.
[0115] In the positive electrode, the positive electrode active material layer may have a porosity of 10% to 40%, particularly 15% to 35%, and more particularly 25% to 30%. In this case, no additional thickness change occurs during the calendering process.
[0116] <Method for Preparing Positive Electrode>
[0117] A method for preparing a positive electrode according to another embodiment of the present invention comprises:
[0118] Step P1: disposing a transfer stack including a base film and a lithium metal layer disposed on the base film on a preliminary positive electrode including a preliminary positive electrode active material layer to form a positive electrode structure, such that the lithium metal layer and the preliminary positive electrode active material layer are in contact with each other;
[0119] Step P2: rolling the positive electrode structure; and
[0120] Step P3: Preparation of the positive electrode by removing the base film from the transfer stack after calendering,
[0121] Here, the pressure applied to the positive electrode structure during the rolling may be in the range of 10 kgf / cm to 90 kgf / cm.
[0122] (1) Step P1
[0123] Reference Figure 1 , the transfer stack 300 may include a base film 310 and a lithium metal layer 320 disposed on the base film 310. As long as the base film 310 is a material that can withstand the high temperature conditions occurring during the deposition of the lithium metal layer 320 on the base film 310, the base film 310 may be used without limitation. Specifically, the base film may include at least one selected from the group consisting of polyethylene terephthalate (PET), polyimide (PI), poly(methyl methacrylate) (PMMA), polypropylene, polyethylene, and polycarbonate.
[0124] The lithium metal layer may be disposed on the base film. The lithium metal layer serves to supply lithium ions to the preliminary positive electrode active material layer. The lithium metal layer contains solid-phase lithium metal, and the lithium metal layer may be specifically formed of solid-phase lithium metal.
[0125] In the transfer stack, the thickness of the lithium metal layer may be 1.0 μm to 10.0 μm, particularly 3.0 μm to 9.0 μm, and more particularly 4.0 μm to 6.5 μm. In the case where the above range is satisfied, the degree of cracking of the positive electrode active material particles on the surface of the positive electrode can be reduced, so that the reduction in the initial capacity of the battery can be suppressed.
[0126] Lithium metal layer loading (unit: mAh / cm 2 ) can be the loading amount of the prepared positive electrode active material layer (unit: mAh / cm 2 ), specifically 12% to 35%, and more specifically 20% to 30%. When the above range is met, the target lithium insertion capacity can be easily achieved because the generation of by-products is small and lithium is easily inserted into the positive electrode active material.
[0127] In step P1, refer to Figure 1 , the preliminary positive active material layer 120 ′ is disposed on the positive current collector 110 , and the transfer stack 300 may be disposed on the preliminary positive active material layer 120 ′ to form a positive electrode structure 400 such that the lithium metal layer 320 and the preliminary positive active material layer contact each other.
[0128] Herein, the positive electrode current collector 110 is the same as the positive electrode current collector described in the above-mentioned positive electrode-related embodiment.
[0129] Reference Figure 2, the transfer stack 300 may further include a polymer layer 330. The polymer layer 330 may be disposed between the base film 310 and the lithium metal layer 320. The polymer layer may effectively peel off the lithium metal layer from the transfer stack during the preparation of the positive electrode and make the lithium metal layer easily transferred to the positive electrode active material layer. That is, the polymer layer may be separated from the transfer stack together with the lithium metal layer to be disposed on the positive electrode active material layer. The polymer layer may be in contact with the positive electrode active material layer, or the lithium metal layer may be present between the polymer layer and the positive electrode active material layer.
[0130] The polymer layer may be at least one selected from the group consisting of polyethylene terephthalate (PET), polyimide (PI), poly(methyl methacrylate) (PMMA), polypropylene, polyethylene, and polycarbonate. Therefore, in a secondary battery comprising a positive electrode, since the polymer layer can be dissolved in the electrolyte contained in the secondary battery, the resistance of the battery can be prevented from increasing. In particular, the polymer layer may include PMMA, in which case the above-mentioned effect may be further improved.
[0131] The thickness of the polymer layer may be 0.1 μm to 10.0 μm, particularly 0.5 μm to 5.0 μm, and more particularly 1.0 μm to 2.5 μm. When the above range is satisfied, the lithium metal layer can be easily transferred to the positive active material layer, and the reverse transfer phenomenon in which the positive active material layer is transferred to the transfer stack can be prevented.
[0132] (2) Step P2
[0133] Reference Figure 3 , in step P2, the prepared positive electrode structure 400 may be calendered. The calendering may be performed by a rolling method. Specifically, by passing two rollers R spaced apart from each other by a predetermined space in the vertical direction, pressure may be applied in the vertical direction to the positive electrode structure 400 passing through the space, and the pressure may be a linear pressure. Through the calendering process, at least a portion of the lithium ions of the lithium metal layer contained in the transfer stack may be embedded in the prepared positive electrode active material layer. In this process, the prepared positive electrode active material layer may become the positive electrode active material layer. In Figure 3 and Figure 4 In FIG. 1 , it is indicated that the lithium metal layer is contained in the positive electrode, but in the case where the entire lithium metal layer is embedded in the preliminary positive electrode active material layer during the rolling process, the lithium metal layer may not exist as a separate layer.
[0134] The pressure applied to the positive electrode structure during rolling may be in the range of 10 to 90 kgf / cm, specifically 15 to 80 kgf / cm, more specifically 20 to 60 kgf / cm, and may more preferably be in the range of 20 to 50 kgf / cm.
[0135] If the pressure during rolling is less than 10 kgf / cm, it is difficult to insert lithium into the positive electrode at a desired level because the lithium metal layer of the transfer stack is not effectively transferred to the positive electrode during the preparation of the positive electrode.
[003] / I
[200] Therefore, because the amount of lithium transferred to the negative electrode during the activation process is reduced, and a large amount of lithium by-products are generated because lithium remains on the surface without diffusing into the active material layer, it is difficult to improve the life characteristics of the battery, and the resistance of the electrode may also increase.
[0136] On the contrary, if the pressure during rolling is greater than 90 kgf / cm, cracking of the positive electrode active material may occur excessively because the diffusion rate of lithium is too large, and accordingly, the positive electrode capacity may decrease and the life characteristics of the battery may deteriorate. In addition, even in this case, there is a problem of an increase in damaged positive electrode active materials, a large amount of lithium by-products may be formed due to a side reaction in which Li2MO2 crystals decompose into Li2O and MO to reduce the capacity of the positive electrode and deteriorate the long-term life characteristics of the battery, and since the rock salt phase also increases, problems such as reduced capacity, increased resistance, and shortened life may occur. For example, if the pressure during rolling is greater than 90 kgf / cm, I
[003] / I
[200] Probably less than 1.2.
[0137] (3) Step P3
[0138] Reference Figure 4 In step P3, the positive electrode 100 may be prepared by removing the base film 310 from the transfer stack after the calendering performed in step P2. In the case where the polymer layer 330 is disposed between the base film 310 and the lithium metal layer 320, the base film 310 may be more easily removed from the polymer layer 330.
[0139] In addition, the method for preparing a positive electrode may further include step P4: leaving the prepared positive electrode to stand (place) for 1 minute to 600 minutes, specifically 1 minute to 30 minutes. Step P4 may be performed after step P2. Specifically, step P4 may be performed in at least one step of "between step P2 and step P3" and "immediately after step P3". Because the reaction heat generated by the reaction of the lithium metal layer with the prepared positive electrode active material layer in step P2 can be effectively released by step P4, lithium is uniformly embedded in the positive electrode, thereby reducing the generation of by-products.
[0140] Since the prepared positive electrode is the same as that of the above-described embodiment, a detailed description thereof will be omitted.
[0141] In the method for preparing the positive electrode of the present embodiment, a lithium metal layer is provided on the positive electrode by a transfer method, and rolling is performed under a pressure of 10 kgf / cm to 90 kgf / cm to insert lithium ions of the lithium metal layer into the preliminary positive electrode active material layer. As a result, lithium-containing byproducts such as Li3N are generated in the positive electrode, and the positive electrode satisfies 1.2≤I
[003] / I
[200] ≤2.0. If a preliminary secondary battery is prepared by using a positive electrode prepared by the above method and the preliminary secondary battery is activated, the lithium ions embedded in the positive electrode are transferred to the negative electrode, so the lithium ions react and fill the irreversible sites of the negative electrode. Therefore, the amount of lithium ions embedded in the negative electrode during battery operation can be appropriately reduced to the level required for battery operation. Therefore, because the available range of the negative electrode capacity can be reduced while maintaining the battery capacity, the excessive volume change of the silicon-based active material particles can be suppressed, and the life characteristics of the battery can be improved. One of the characteristics of the present invention is that the pre-lithiation is not carried out by contacting the lithium metal layer with the negative electrode as usual, but the lithium metal layer is transferred to the positive electrode and rolled, and then the lithium ions embedded in the positive electrode are transferred to the negative electrode during the activation process of the battery. That is, the negative electrode is not in contact with the lithium metal layer, and the lithium ions are not directly embedded in the negative electrode from the lithium metal layer. Therefore, the phenomenon of excessive heat generated due to the alloying reaction of lithium and silicon at the negative electrode can be avoided, and the possibility of fire caused by the reaction between lithium and moisture can be significantly reduced. Furthermore, because lithium ions are not inserted into the negative electrode during the slotting and punching of the negative electrode (because no pre-lithiation is performed), the possibility of fire during the slotting and punching process can be significantly reduced.
[0142] As described above, during the preparation of the positive electrode, lithium ions in the lithium metal layer are embedded in the positive electrode active material layer at an appropriate level of pressure (10 kgf / cm to 90 kgf / cm), so that the degree of cracking of the positive electrode active material can be reduced, thereby improving the life characteristics and energy density of the lithium ion secondary battery. In addition, since the excessive generation of lithium by-products can be suppressed to reduce the loss amount of lithium, the long-term life characteristics of the battery can be improved.
[0143] <Lithium-ion secondary battery>
[0144] The lithium ion secondary battery according to an embodiment of the present invention includes: a positive electrode; a negative electrode; a separator disposed between the positive electrode and the negative electrode; and an electrolyte, wherein the positive electrode includes a positive electrode active material layer, the positive electrode active material layer includes a positive electrode active material, and the positive electrode can satisfy the following Formula 1.
[0145] [Formula 1]
[0146] 1.2 ≤ I
[003] / I
[200] ≤ 2.0
[0147] In Formula 1,
[0148] I
[003] is the integrated value of the maximum peak that appears in the 2θ range of 17.0° to 19.0° during the XRD measurement on the surface of the positive electrode active material layer, and
[0149] I
[200] is the integrated value of the maximum peak that appears in the 2θ range of 43° to 45° during the XRD measurement on the surface of the positive electrode active material layer.
[0150] Since the positive electrode is the same as the positive electrode of the above embodiment, its description will be omitted.
[0151] The negative electrode includes a negative electrode active material layer, and the negative electrode active material layer may include a negative electrode active material.
[0152] The negative electrode active material may include a silicon-based negative electrode active material. The silicon-based negative electrode active material may include at least one of Si and SiO x (0 < x < 2).
[0153] Si is silicon particles, where it may be silicon particles (particles formed of silicon), so-called pure silicon. The silicon particles can effectively improve the capacity of the negative electrode. SiO x (0 < x < 2) may be in a form including Si and SiO2, and Si may form a phase. That is, x corresponds to the number ratio of oxygen (O) to Si contained in SiO2 (0 < x < 2). Among them, the silicon-based composite particles include SiO x(When 0 < x < 2), the discharge capacity of the secondary battery can be improved.
[0154] The positive electrode included in the lithium ion secondary battery of the present embodiment can satisfy the above formula 1. Herein, this means that the positive electrode is prepared by the method for preparing the positive electrode of the above embodiment. In particular, lithium is transferred to the positive electrode at an appropriate level of pressure. Furthermore, in the case where the negative electrode includes a silicon-based negative electrode active material, the fact that the positive electrode satisfies formula 1 has greater significance. If the positive electrode prepared by the above method for preparing the positive electrode is included in the secondary battery and then subjected to an activation process, since a predetermined amount of lithium ions are transferred from the positive electrode to the silicon-based negative electrode active material of the negative electrode, the excessive volume change of the silicon-based active material during battery operation can be suppressed and the life characteristics of the battery can be improved. In addition, since no separate lithium metal layer is transferred to the negative electrode, the negative electrode and the lithium metal layer do not contact each other and lithium ions are not directly embedded in the negative electrode from the lithium metal layer. Therefore, the phenomenon of excessive heat generation due to the alloying reaction between lithium and silicon at the negative electrode can be avoided, and the possibility of ignition due to the reaction between lithium and moisture can be significantly reduced. Furthermore, since lithium ions are not embedded in the negative electrode during the grooving and punching of the negative electrode (because prelithiation is not performed), the possibility of ignition during the grooving and punching process can be significantly reduced.
[0155] The negative electrode active material may further include a carbon-based negative electrode active material. The carbon-based negative electrode active material may include at least one selected from artificial graphite, natural graphite, and graphitized mesophase carbon microspheres.
[0156] The negative electrode active material layer may further include a negative electrode binder. The negative electrode binder may include at least one selected from the following: polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylate, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and materials in which hydrogen thereof is replaced by lithium (Li), sodium (Na), or calcium (Ca), or may include various copolymers thereof.
[0157] The negative electrode active material layer may also contain a negative electrode conductive material. There is no particular limitation on the negative electrode conductive material, as long as it has conductivity without causing adverse chemical changes in the battery, and for example, conductive materials such as the following may be used: graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers or metal fibers; conductive tubes such as carbon nanotubes; fluorocarbons; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or polyphenylene derivatives.
[0158] The separator separates the negative electrode from the positive electrode and provides a path for the movement of lithium ions, wherein any separator can be used as the separator without particular limitation, as long as it is commonly used in secondary batteries, and in particular, a separator having high moisture retention capacity for electrolytes and low resistance to electrolyte ion migration is preferred. Specifically, porous polymer films, such as porous polymer films prepared from polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers, can be used; or a laminated structure having two or more layers thereof. In addition, a typical porous non-woven fabric can be used, such as a non-woven fabric formed of high melting point glass fiber or polyethylene terephthalate fiber. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a single-layer or multilayer structure can be optionally used.
[0159] The electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten inorganic electrolyte that can be used to prepare a lithium secondary battery, but the present invention is not limited thereto.
[0160] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.
[0161] Examples of the nonaqueous organic solvent may be aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.
[0162] Especially, in carbonate organic solvents, cyclic carbonates such as ethylene carbonate and propylene carbonate have high dielectric constant as high viscosity organic solvent and lithium salt is well dissociated in electrolyte, thus can preferably use cyclic carbonates.Because when cyclic carbonates are mixed with low viscosity, low dielectric constant linear carbonates such as dimethyl carbonate and diethyl carbonate in appropriate proportion, can prepare electrolyte with high conductivity, so can more preferably use cyclic carbonates.
[0163] A lithium salt can be used as the metal salt, and the lithium salt is a material that is easily soluble in a non-aqueous electrolyte. As an anion of the lithium salt, for example, at least one selected from the following can be used: - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .
[0164] In order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity, and improve the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, at least one additive may be included in the electrolyte, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.
[0165] <Method for preparing lithium ion secondary battery>
[0166] A method for preparing a lithium ion secondary battery according to one embodiment of the present invention includes:
[0167] Step B1: preparing a preliminary lithium ion secondary battery, the preliminary lithium ion secondary battery comprising a positive electrode; a negative electrode; a separator disposed between the positive electrode and the negative electrode; and an electrolyte; and
[0168] Step B2: Activate the prepared lithium-ion secondary battery,
[0169] The method for preparing the positive electrode comprises:
[0170] Step P1: disposing a transfer stack including a base film and a lithium metal layer disposed on the base film on a preliminary positive electrode including a preliminary positive electrode active material layer to form a positive electrode structure, such that the lithium metal layer and the preliminary positive electrode active material layer are in contact with each other;
[0171] Step P2: rolling the positive electrode structure; and
[0172] Step P3: Removing the base film from the transfer stack after calendering,
[0173] Here, the pressure applied to the positive electrode structure during the rolling may be in the range of 10 kgf / cm to 90 kgf / cm.
[0174] Here, the secondary battery may be the same as the secondary battery in the above-described embodiment.
[0175] Since the positive electrode is the same as that of the above-described embodiment, and the method of preparing the positive electrode is the same as the above-described method of preparing the positive electrode, a description thereof will be omitted.
[0176] Since the negative electrode is the same as that of the above-described embodiment, a description thereof will be omitted.
[0177] In step B1, the preparatory lithium ion secondary battery may include a positive electrode and a negative electrode. Specifically, the preparatory lithium ion secondary battery may include a positive electrode, a negative electrode, a separator and an electrolyte. Specifically, the positive electrode and the negative electrode are spaced apart from each other and stacked with a separator therebetween, and may be impregnated with an electrolyte. The negative electrode before undergoing the activation process may be a preparatory negative electrode, and refers to a state in which lithium ions have not yet been embedded. The preparatory lithium ion secondary battery refers to a battery before undergoing the activation process.
[0178] The method for preparing a positive electrode may further include step P4: leaving the prepared positive electrode to stand (place) for 1 minute to 600 minutes, specifically 1 minute to 30 minutes. Step P4 may be performed after step P2. Specifically, step P4 may be performed in at least one step of "between step P2 and step P3" and "immediately after step P3". Because the reaction heat generated by the reaction of the lithium metal layer with the prepared positive electrode active material layer in step P2 can be effectively released by step P4, lithium is uniformly embedded in the positive electrode, thereby having the effect of reducing the generation of by-products.
[0179] Step B2 may include applying current to the prepared lithium ion secondary battery. The prepared lithium ion secondary battery may be activated by the current, and lithium ions may be intercalated into the negative electrode to achieve pre-lithiation of the negative electrode.
[0180] According to another embodiment of the present invention, a battery module including a lithium ion secondary battery as a unit cell and a battery pack including the battery module are provided. Because the battery module and the battery pack include lithium ion secondary batteries having high capacity, high rate performance and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the following: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems.
[0181] Hereinafter, preferred embodiments will be provided to better understand the present invention. It will be apparent to those skilled in the art that these embodiments are provided only to illustrate the present invention, and various variations and changes are possible within the scope and technical spirit of the present invention. Such variations and changes fall within the scope of the claims included herein.
[0182] Examples and Comparative Examples
[0183] Example 1-1: Preparation of positive electrode
[0184] A transfer stack was prepared, which included a PET film (base film), a polymer layer (2.5 μm thick) formed of PMMA disposed on the PET film, and a lithium metal layer (6 μm thick, with a loading of 1.24 mAh / cm) disposed on the polymer layer and formed of solid-phase lithium metal. 2 ).
[0185] Using Li[Ni 0.86 Co 0.05 Mn 0.08 Al 0.01 ]O2 as the positive electrode active material. The positive electrode active material is a plurality (more than 10) of Li[Ni 0.86 Co 0.05 Mn 0.08 Al0.01 ]O2 primary particles are in the form of secondary particles bonded to each other, and the average particle size of the secondary particles is D 50 The positive electrode was prepared, the positive electrode comprising a preliminary positive electrode active material layer and an aluminum foil (thickness: 12 μm) as a positive electrode current collector, the preliminary positive electrode active material layer comprising a positive electrode active material, PVdF as a positive electrode binder, and carbon nanotubes as a positive electrode conductive material in a weight ratio of 98:1:1. The loading capacity of the preliminary positive electrode active material layer was 4.5 mAh / cm 2 And the thickness is 140 μm.
[0186] The transfer stack is disposed on the preliminary positive electrode active material layer so that the lithium metal layer is in contact with the preliminary positive electrode active material layer.
[0187] Thereafter, the positive electrode on which the transfer stack is disposed is rolled by a roller pressing method and then left to stand for 24 hours. The pressure during the rolling process is 20 kgf / cm, whereby the lithium ions of the lithium metal layer are embedded in the prepared positive electrode active material layer to form a positive electrode active material layer. Thereafter, the base film is removed and the rolled positive electrode is left to stand for 10 minutes to prepare a positive electrode comprising a positive electrode current collector, a positive electrode active material layer and a polymer layer.
[0188] Example 1-2: Preparation of positive electrode
[0189] A positive electrode was prepared in the same manner as in Example 1-1, except that the pressure during rolling was 50 kgf / cm instead of 20 kgf / cm.
[0190] Example 1-3: Preparation of positive electrode
[0191] A positive electrode was prepared in the same manner as in Example 1-1, except that the pressure during rolling was 30 kgf / cm instead of 20 kgf / cm.
[0192] Example 1-4: Preparation of positive electrode
[0193] A positive electrode was prepared in the same manner as in Example 1-1, except that the pressure during rolling was 10 kgf / cm instead of 20 kgf / cm.
[0194] Example 1-5: Preparation of positive electrode
[0195] A positive electrode was prepared in the same manner as in Example 1-1, except that the pressure during rolling was 90 kgf / cm instead of 20 kgf / cm.
[0196] Comparative Example 1-1: Preparation of positive electrode
[0197] A positive electrode was prepared in the same manner as in Example 1-1, except that the pressure during rolling was 5 kgf / cm instead of 20 kgf / cm.
[0198] Comparative Example 1-2: Preparation of positive electrode
[0199] A positive electrode was prepared in the same manner as in Example 1-1, except that the pressure during rolling was 120 kgf / cm instead of 20 kgf / cm.
[0200] Comparative Example 1-3: Preparation of positive electrode
[0201] A positive electrode was prepared in the same manner as in Example 1-1, except that the pressure during rolling was 100 kgf / cm instead of 20 kgf / cm.
[0202] Comparative Example 1-4: Preparation of negative electrode
[0203] A transfer stack was prepared, which included a PET film (base film), a polymer layer (1 μm thick) formed of PMMA disposed on the PET film, and a lithium metal layer (3 μm thick, with a loading of 0.6 mAh / cm) disposed on the polymer layer and formed of solid-phase lithium metal. 2 ).
[0204] Average particle size D 50 A negative electrode was prepared, wherein the negative electrode included a preliminary negative electrode active material layer, wherein the preliminary negative electrode active material layer included a negative electrode active material, carboxymethyl cellulose (CMC) as a negative electrode binder, and carbon nanotubes as a negative electrode conductive material in a weight ratio of 80:10:10. The loading capacity of the preliminary negative electrode active material layer was 10 mAh / cm 2 And the thickness is 75 μm.
[0205] The transfer stack is disposed on the preliminary negative electrode active material layer so that the lithium metal layer is in contact with the preliminary negative electrode active material layer.
[0206] Thereafter, the negative electrode on which the transfer stack was disposed was rolled by a roll-to-roll method and then left to stand for 24 hours. Thus, lithium ions in the lithium metal layer were inserted into the preliminary negative electrode active material layer to form a negative electrode active material layer. The pressure during the rolling process was 50 kgf / cm.
[0207] Thereafter, the base film is removed to prepare a negative electrode including a negative electrode active material layer and a polymer layer.
[0208] Experimental Example 1: I
[003] / I
[200] Measurement
[0209] For Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-4, XRD was measured by the following method to confirm I
[003] / I
[200] , and I
[003] / I
[200] As shown in Table 1. Figure 5 , Figure 6 and Figure 7 It is a graph showing the XRD results of Examples 1-1 and 1-2 and Comparative Example 1-2.
[0210] The wavelength of X-rays generated by Cu Kα was used, and the wavelength (λ) of the light source was 0.15406 nm.
[0211] 1) Measurement equipment and conditions: Bruker D8 Endeavor (Cu target 40 kV, 40 mA, 1.54 Å) LynxEye position sensitive detector (4.1° slit)
[0212] 2) Experimental process
[0213] 2-1) Preparation for cutting / cross sectioning: Prepare the sample by cutting it to the size of the sample holder.
[0214] 2-2) Preparation for sample mounting: The sample (positive electrode) was adhered to a glass plate using double-sided tape so that there was no gap therebetween, and then mounted using rubber clay and a holder formed of PMMA.
[0215] 2-3) Powder XRD (Bruker D8 Endeavor): The fixed divergence slit (FDS) was adjusted to 0.5° according to the sample size, and the powder XRD was measured every 0.0156° in the 2θ range of 10° to 125° for 0.3 seconds.
[0216] 2-4) XRD phase analysis: Determine the phases present in the sample by comparing with a database (PDF).
[0217] 2-5) Rietveld analysis: Rietveld refinement is performed using a complete structural model of the phases present in the sample.
[0218] Example 2-1: Preparation of secondary battery
[0219] Average particle size D 50 A negative electrode was prepared comprising a preliminary negative electrode active material layer, wherein the preliminary negative electrode active material layer comprises a negative electrode active material, carboxymethyl cellulose (CMC) as a negative electrode binder, and carbon nanotubes as a negative electrode conductive material in a weight ratio of 80:10:10. The loading amount of the preliminary negative electrode active material layer is 10 mAh / cm2 , and the thickness is 75 μm.
[0220] The positive electrode, negative electrode and porous polyethylene separator of Example 1-1 were assembled using a winding method, and a preliminary lithium ion secondary battery was prepared by injecting electrolyte (ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 3 / 7 (volume ratio) and lithium hexafluorophosphate (LiPF6 1 mol)) into the assembled battery.
[0221] The prepared lithium ion secondary battery was charged to 4.2 V at a C rate of 0.1 C and then discharged to 2.5 V to perform an activation process.
[0222] Example 2-2: Preparation of secondary battery
[0223] A lithium ion secondary battery was prepared in the same manner as in Example 2-1, except that the positive electrode of Example 1-2 was used instead of the positive electrode of Example 1-1.
[0224] Example 2-3: Preparation of secondary battery
[0225] A lithium ion secondary battery was prepared in the same manner as in Example 2-1, except that the positive electrode of Example 1-3 was used instead of the positive electrode of Example 1-1.
[0226] Example 2-4: Preparation of secondary battery
[0227] A lithium ion secondary battery was prepared in the same manner as in Example 2-1, except that the positive electrode of Example 1-4 was used instead of the positive electrode of Example 1-1.
[0228] Example 2-5: Preparation of secondary battery
[0229] A lithium ion secondary battery was prepared in the same manner as in Example 2-1, except that the positive electrode of Example 1-5 was used instead of the positive electrode of Example 1-1.
[0230] Comparative Example 2-1: Preparation of secondary battery
[0231] A lithium ion secondary battery was prepared in the same manner as in Example 2-1, except that the positive electrode of Comparative Example 1-1 was used instead of the positive electrode of Example 1-1.
[0232] Comparative Example 2-2: Preparation of secondary battery
[0233] A lithium ion secondary battery was prepared in the same manner as in Example 2-1, except that the positive electrode of Comparative Example 1-2 was used instead of the positive electrode of Example 1-1.
[0234] Comparative Example 2-3: Preparation of secondary battery
[0235] A lithium ion secondary battery was prepared in the same manner as in Example 2-1, except that the positive electrode of Comparative Example 1-3 was used instead of the positive electrode of Example 1-1.
[0236] Comparative Example 2-4: Preparation of Secondary Battery
[0237] Using Li[Ni 0.86 Co 0.05 Mn 0.08 Al 0.01 ]O2 as the positive electrode active material. The positive electrode active material is a plurality (more than 10) of Li[Ni 0.86 Co 0.05 Mn 0.08 Al 0.01 ]O2 primary particles are in the form of secondary particles bonded to each other, and the average particle size of the secondary particles is D 50 The positive electrode was prepared, wherein a preliminary positive electrode active material layer was provided on an aluminum foil (thickness: 12 μm), and the preliminary positive electrode active material layer contained a positive electrode active material, PVdF as a positive electrode binder, and carbon nanotubes as a positive electrode conductive material in a weight ratio of 98:1:1. The loading capacity of the preliminary positive electrode active material layer was 4.5 mAh / cm 2 And the thickness is 140 μm.
[0238] The negative electrode, positive electrode and porous polyethylene separator of Comparative Examples 1-4 were assembled using a winding method, and a lithium ion secondary battery was prepared by injecting electrolyte (ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 1 / 2 (volume ratio) and lithium hexafluorophosphate (LiPF6 1 mol)) into the assembled battery.
[0239] Experimental Example 2: Measurement of Lithium Loss
[0240] The lithium loss amounts were measured for the lithium ion secondary batteries of Examples 2-1 to 2-5 and Comparative Examples 2-1 to 2-4, and are shown in Table 1.
[0241] First, the initial charge capacity of a positive electrode in which lithium ions were not transferred and intercalated (preliminary positive electrode used in Example 1-1) as a control group and the initial charge capacity of the positive electrode of Example 2-1 were measured under the following conditions.
[0242] After constant current / constant voltage (CC / CV) charging to 4.2 V at 0.1 C, the 0.05 C cut-off
[0243] CC discharge to 2.3 V at 0.1 C
[0244] The theoretical capacity of the lithium metal layer used in the experiment is 1 mAh / cm 2 .
[0245] The lithium loss amount was calculated using the following formula.
[0246] Lithium loss (%) = [1-{(initial charge capacity of the positive electrode of Example 2-1-initial charge capacity of the positive electrode of the control group) / theoretical capacity of the lithium metal layer}] × 100
[0247] Similarly, this method was performed on the remaining Examples and Comparative Examples 2-1 to 2-3.
[0248] Regarding Comparative Example 2-4, the lithium loss amount of the negative electrode was measured in the same manner as above.
[0249] Experimental Example 3: Evaluation of Life Characteristics (Capacity Retention Rate)
[0250] Each of the lithium ion secondary batteries of Examples 2-1 to 2-5 and Comparative Examples 2-1 to 2-4 was charged and discharged to evaluate life characteristics (capacity retention rate).
[0251] Charging conditions: charged to 4.2 V at a current density of 1 C
[0252] Discharge conditions: Discharge to 2.5 V at a current rate of 0.5 C
[0253] Each capacity retention ratio was calculated as follows.
[0254] Capacity retention rate (%) = (100th discharge capacity / first discharge capacity) × 100
[0255]
[0256] Referring to Table 1, for the embodiments in which the calendering is performed under a pressure satisfying the range of 10 kgf / cm to 90 kgf / cm during calendering, it can be understood that I
[003] / I
[200] The range of 1.2 to 2.0 is satisfied, the amount of lithium loss is low, and the capacity retention rate is high, and it can be understood that, compared with Comparative Example 2-4 in which pre-lithiation is directly performed on the negative electrode, safety and process advantages can be ensured, and excellent effects can also be expected. On the contrary, for Comparative Example 2-1 in which the calendering pressure applied is 5 kgf / cm, it can be understood that the rock salt phase formed is relatively less than that in the embodiment, but the amount of lithium loss is doubled due to the generation of a large amount of lithium by-products, and accordingly, it can be confirmed that the life characteristics are also deteriorated. In addition, Comparative Examples 2-2 and 2-3 in which the calendering pressure applied is greater than 90 kgf / cm show a large amount of lithium loss, but this is due to the cracking phenomenon of the positive electrode active material particles and the decomposition of the Li2MO2 phase caused by over-lithiation, which can be seen from I
[003] / I
[200] From the fact that φ has a value smaller than 1.2, it can be understood that the life characteristics are also deteriorated accordingly.
[0257] [Explanation of Reference Numerals]
[0258] 110: Positive electrode collector
[0259] 120, 120': preparing positive electrode active material layer
[0260] 300: Transfer stack
[0261] 310: Base film
[0262] 320: Lithium metal layer
[0263] 330: Polymer layer
[0264] 400: Positive electrode structure
[0265] R: Roller
Claims
1. A positive electrode, comprising a positive electrode active material layer, wherein the positive electrode active material layer comprises a positive electrode active material, and The positive electrode satisfies Formula 1: [Formula 1] 1.2≤I [003] / I [200] ≤2.0 in, In formula 1, I [003] is the integrated value of the maximum peak in the 2θ range of 17.0° to 19.0° appearing during XRD (X-ray diffraction) measurement on the surface of the positive electrode active material layer, and I [200] It is an integrated value of the maximum peak in the 2θ range of 43° to 45° appearing during XRD measurement on the surface of the positive electrode active material layer.
2. The positive electrode according to claim 1, in, The positive electrode active material layer comprises at least one selected from the following: Li 3 N.Li 2 CO 3 and LiOH.
3. The positive electrode according to claim 1, in, The positive electrode active material includes a layered structured lithium nickel-based transition metal composite oxide, and the lithium nickel-based transition metal composite oxide includes a compound of Chemical Formula 1: [Chemical formula 1] Li 1+x [Ni a Co b Mr c M 1 (1-a-b-c) ]O (2-d) A d Wherein, in Chemical Formula 1, M 1 is at least one selected from Al, Mg, Cr, Ti, Si and Y, A is at least one selected from F, P and Cl, and -0.5≤x≤0.5, 0.6≤a<1, 0.03≤b≤0.1, 0.03≤c≤0.1, 0≤d≤0.1 and 0 <a+b+c≤1。 4. The positive electrode according to claim 1, in, The positive electrode active material comprises a layered structured lithium nickel-based transition metal composite oxide, and the lithium nickel-based transition metal composite oxide has a D 50 .
5. The positive electrode according to claim 1, in, The positive electrode active material includes a layered structured lithium nickel-based transition metal composite oxide, and the lithium nickel-based transition metal composite oxide is in the form of secondary particles in which a plurality of primary particles are bonded to each other. 6 . The positive electrode according to claim 1 , further comprising at least one layer selected from a lithium metal layer and a polymer layer provided on the positive electrode active material layer.
7. A method for preparing a positive electrode, the method include: Step P1: disposing a transfer stack including a base film and a lithium metal layer disposed on the base film on a preliminary positive electrode including a preliminary positive electrode active material layer to form a positive electrode structure, such that the lithium metal layer and the preliminary positive electrode active material layer are in contact with each other; Step P2: rolling the positive electrode structure; and Step P3: removing the base film from the transfer stack after the calendering, wherein a pressure applied to the positive electrode structure during the rolling is in a range of 10 kgf / cm to 90 kgf / cm.
8. The method according to claim 7, in, In step P2, The calendering is performed by a roll pressing method.
9. The method according to claim 7, in, The lithium metal layer has a thickness of 1 μm to 10 μm.
10. The method according to claim 7, in, The loading amount of the lithium metal layer is 4% to 40% of the loading amount of the preliminary positive electrode active material layer.
11. The method according to claim 7, in, The transfer stack further comprises a polymer layer, and The polymer layer is disposed between the base film and the lithium metal layer.
12. The method according to claim 11, in, The polymer layer includes at least one selected from the group consisting of polyethylene terephthalate, polyimide, poly(methyl methacrylate), polypropylene, polyethylene, and polycarbonate.
13. A lithium secondary battery comprising a positive electrode; a negative electrode; a separator disposed between the positive electrode and the negative electrode; and an electrolyte, in, The positive electrode comprises a positive electrode active material layer, the positive electrode active material layer comprises a positive electrode active material, and The positive electrode satisfies Formula 1: [Formula 1] 1.2≤I [003] / I [200] ≤2.0 In formula 1, I [003] is the integrated value of the maximum peak in the 2θ range of 17.0° to 19.0° appearing during XRD (X-ray diffraction) measurement on the surface of the positive electrode active material layer, and I [200] It is an integrated value of the maximum peak in the 2θ range of 43° to 45° appearing during XRD measurement on the surface of the positive electrode active material layer.
14. The lithium secondary battery according to claim 13, in, The negative electrode comprises a negative electrode active material layer, and The negative electrode active material layer includes a silicon-based negative electrode active material.
15. The lithium secondary battery according to claim 13, in, The silicon-based negative electrode active material is pure silicon (Si).
